Population dynamics of the pioneer population of Daphnia parvula, Fordyce during the invasion of Lake Candia (Northern Italy) - Fiorenza MARGARITORA; Bruno COUCHAUD; Gianluigi GIUSSANI; Nicoletta RICCARDI (Journal of Limnology, 2004)
Since the 1970s Daphnia parvula, Fordyce, originally distributed in the New World, has been invading Europe. In Italy D. parvula first appeared in the shallow, eutrophic Lake Candia (Piedmont, Northern Italy) during September 2002. Although several studies have documented D. parvula dispersal in European habitats, little is known about the life cycle and ecology of this invader in its new habitats. Invasion success depends on the ability of the invader population to perform well in the new ecosystem, which in turn results from the interaction between the characteristics of the invader and those of the invaded environment and its resident community. Early detection of D. parvula in the intensively studied Lake Candia offered an excellent opportunity to study the performance of the pioneer population and to document the early phases of invasion. Following the dynamics of the pioneer D. parvula population provided evidence of a high level of gamogenetic reproduction during most periods of population development. The production of males started at the onset of population growth prior to ephippia formation. The sex ratio ranged from 0.1 to 0.33 males per female with a maximum in October when males accounted for up to 24% of the total population density. The percentage of ephippia (free ephippia + ephippial females) out of the total population density ranged from 3 to 23%. The large pool of resting eggs produced by the pioneer population of D. parvula in Lake Candia might reflect a strategy for increasing the probability of survival and establishment in the new environment.